Komentarz do bibliografii przekładów literatury polskiej w Serbii i serbskiej w Polsce w 2015 roku - Sobalkowska, Estera (Przekłady Literatur Słowiańskich, 2016)
Comments to the Polish‑Serbian bibliography in 2015 The text analyses the issue of Polish literature in Serbia and Serbian literature in Poland. Most of the translations that appeared in Serbia in 2015 were reprints of previous editions or new, contemporized translations of works already known in the Serbian publishing market. The year 2015 saw 23 book publications (without any volume of poetry) and 17 poems in various magazines. Serbian literature was poorly represented in the discussed time — only two comics, two anthologies of poetry and 23 poems were published. Consequently, there was not a single prose publication. This is a tendency, as in 2014, not a single translation of Serbian prose in Polish publishing market appeared. Key words: Polish literature, Serbian literature, poetry, book publications, comic, translation